ANALISIS KEBUTUHAN UAP PADA STASIUN STERILIZER DI PABRIK KELAPA SAWIT - Edi Siswanto, Jatmiko; A, Topan (ITP Press, 2023)
In palm oil processing, one of the processes is boiling using a sterilizer machine, where the sterilizer is a steam vessel used to boil FFB with steam pressure in accordance with the standard working pressure that is permitted, as well as in boiling palm oil marks in a sterilizer that has factors or variables. in boiling namely Boiling Capacity (Q), Boiling Pressure (Peak pressure), Inlet Water Temperature (T.in) and Boiling Time (t). To find out the optimality in the boiling process, research was carried out and data collection on sterilizer operations in the palm oil mill industry obtained data or variables in boiling. From the calculation of the research data, it was found that the working pressure of boiling would affect the steam requirement in the process where at the Peak 1 pressure it required 240,414 kcal/hour of steam, Peak 2 required 705,819 kcal/hour of steam and at Peak 3 it required 859,375 kcal/hour of steam. Optimal Boiling is the largest capacity produced according to the working pressure in the boiling result. The optimal pressure is seen at the greatest pressure of 2.7 bar with the shortest boiling time of 58 minutes. Which produces 9 boils per shift with a capacity of 207 tons and at a pressure of 2.4 Bar it produces 8 boils per shift with a capacity of 84 tons and for a pressure of 1.7 bar it produces 7 boils per shift. with a capacity of 161 tons.